2021
DOI: 10.1007/s13365-021-01013-8
|View full text |Cite
|
Sign up to set email alerts
|

A case-based systematic review on the SARS-COVID-2-associated cerebrovascular diseases and the possible virus routes of entry

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sparked a global pandemic that continues to affect various facets of human existence. Many sources reported virus-induced acute cerebrovascular disorders. Systematically, this paper reviews the case studies of COVID-19-related acute cerebrovascular diseases such as ischaemic stroke, intracerebral hemorrhage, and cerebral sinus thrombosis. We also spoke about how SARS-CoV-2 can infect the brain and trigger the aforementioned disorders. We stated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…It has had also a negative effect on Iran ( 2 , 3 ). During influenza outbreaks, it had been reported that several infected patients died because of complications of comorbid cardiovascular disease (CVD) than for secondary bacterial pneumonia ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has had also a negative effect on Iran ( 2 , 3 ). During influenza outbreaks, it had been reported that several infected patients died because of complications of comorbid cardiovascular disease (CVD) than for secondary bacterial pneumonia ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%